Kailas histories: Renunciate traditions and the construction of himalayan sacred geography - Mckay, Alex (New Delhi Manohar, 2024)
Tibet's Mount Kailas is one of the world's great pilgrimage centres, renowned as an ancient sacred site that embodies a universal sacrality. But Kailas Histories: Renunciate Traditions and the Construction of Himalayan Sacred Geography demonstrates that this understanding is a recent construction by British colonial, Hindu modernist, and New Age interests. Using multiple sources, including fieldwork, Alex McKay describes how the early Indic vision of a heavenly mountain named Kailas became identified with actual mountains.
Keywords: Hindu pilgrims and pilgrimages--China--Kailas; Tibet region--Religious life and customs; Mount. Tibet Autonomous Region (China)--History